Inventing Narratives, Inventorying Natural Resources: Colonial Economic Exploitation in Conradâ€™s Malay Fiction - Adipurwawidjana, Ari J. (Universitas Sanata Dharma, 2020)
Literary narratives had accompanied global economic exploitation of natural resources since the rise of Britain as an imperial force in the late sixteenth century marked by Thomas Hariotâ€™s A Brief and True Report of the New Found Land of Virginia (1588), in which Hariot narrates, describes, and inventories natural and human resources in Virginia to invite economic interest and to justify colonization. The tradition of writing a descriptive overview of conquered lands was then furthered in the late eighteenth and early nineteenth centuries by Marsdenâ€™s History of Sumatra (1783) and Rafflesâ€™s History of Java (1817) as British colonial rule extended to the Malay Archipelago. However, towards the end of the nineteenth century, as economic and political rule inevitably gave way to complex socio-cultural interaction, the fiction of Joseph Conrad set in the Archipelago, being novelistic in nature, provides a more dialogic portrayal of British colonial presence, particularly in Java and Borneo, which goes beyond mere justification for the exploitation of local resources. Following the cue from the work Edward Said in identifying textualization as a mode of colonial intellectual domination and Benita Parry in revealing the â€œghostlyâ€ presence of empire in colonial fiction, I would like to argue that Conradâ€™s Malay fiction both justifies and problematizes the relationship between British colonial enterprise and the natural as well as socio-cultural environment in the Archipelago.